2022
DOI: 10.1002/jad.12027
|View full text |Cite
|
Sign up to set email alerts
|

Family socioeconomic status and provincial‐level economic, educational, and health‐related factors as predictors of present‐ and future‐oriented subjective wellbeing in junior high school students in China

Abstract: Introduction: Previous studies have examined family socioeconomic status (SES) and regional-level factors that predict adolescents' present subjective wellbeing (SWB). However, as adolescents' SWB tends to be future-oriented, this study examined the relationships between family SES and provincial-level economic, educational, and health-related factors and adolescents' present-and future-oriented SWB. Methods: The sample includes 17,341 12-to 17-year-old adolescents (M age = 13.86; SD age = 0.79; 9056 girls and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“… 19 Wu et al found that per capita years of education at the provincial level could positively predict the life satisfaction of middle school students in China. 7 However, another study found that the percentage of education expenditure in regional GDP did not significantly predict adolescent life satisfaction, 11 which may be due to this indicator not being representative of the actual educational resources adolescents obtained. To the best of our knowledge, no other educational factors at the regional level have been examined to determine their potential predictive effect on adolescents’ life satisfaction.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“… 19 Wu et al found that per capita years of education at the provincial level could positively predict the life satisfaction of middle school students in China. 7 However, another study found that the percentage of education expenditure in regional GDP did not significantly predict adolescent life satisfaction, 11 which may be due to this indicator not being representative of the actual educational resources adolescents obtained. To the best of our knowledge, no other educational factors at the regional level have been examined to determine their potential predictive effect on adolescents’ life satisfaction.…”
Section: Introductionmentioning
confidence: 97%
“… 6 Moreover, Wu et al found significant differences in the life satisfaction of junior high school students across China’s 31 provinces. 7 However, why life satisfaction among adolescents differs across regions has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 In addition to school-level factors, regional factors, such as Human Development Index (HDI) scores, have been found to be associated with subjective well-being among youths. 22 According to the livability theory, 23 people in a developed region may benefit from better economic prosperity and educational opportunities, which may be associated with improved mental well-being. 3 Some researchers have found that people in a more-developed society show a better mean level of mental well-being.…”
Section: Introductionmentioning
confidence: 99%